Penerapan Teknologi UAV untuk Pemetaan Kebun Jeruk di Kabupaten Nabire dengan Analisis Spasial Menggunakan ArcGIS - Yuliawan, Kristia; Pilenaung, Jevan (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
This study examines the application of Unmanned Aerial Vehicle (UAV) technology and ArcGIS software in mapping orange orchards in Samabusa, Nabire Regency. The goal was to improve the efficiency and accuracy of farmland mapping by producing high-resolution aerial imagery. The obtained geospatial data were used to construct orthophoto maps, detect the location of citrus and non-citrus plants, and analyze the spatial distribution and topography of the land. The results showed that the integration of UAV and ArcGIS was able to precisely identify 207 citrus plants and 125 non-citrus objects, providing a basis for data-driven decision-making. These findings demonstrate the effectiveness of UAVs as a solution to the limitations of conventional mapping and support more precise and sustainable plantation management in the Nabire Regency area.